MANFAAT KEANEKARAGAMAN HAYATI TERHADAP LINGKUNGAN - THIUR DIANTI SIBORO (LP2MTBM MAKARIOZ, 2019)
The writing of this paper aims to determine the benefits of biodiversity in the environment. Writing method uses the library research method. From the discussion it can be concluded that living things in this world are very diverse. The diversity of biological creatures is called biodiversity or biodiversity. Every river system has a different biodiversity. Biodiversity is indicated by Adany; a variety of shapes, sizes, colors, and properties of other living things. Biodiversity is caused by two factors, namely genetic factors and environmental factors. There is an interaction between genetic factors and environmental factors in influencing the nature of living things. Human activities can reduce biodiversity, both the diversity of genes, the types and diversity of the environment. But in addition, human activities can also increase biodiversity such as reforestation, making urban parks, and breeding. Biodiversity is a constituent component of natural ecosystems that have a very large role in terms of ecological, social, economic and cultural aspects.